Miracle of nature—dialog with nature through artistic creation - Raappana-Luiro, Leena (Frontiers in Communication, 2024)
The aim of this study is to analyse the effect of an illustrator's visual style in representing nature. The focus is on the author's own artistic project in which the personal relationship with nature is reflected. As for theory, the style used in the representation is seen as a combination of semiotic resources. In this case, the style is inspired by historical images: old still life paintings and illustrations from natural encyclopaedias and field guides. The stylistic influences work as a connotative semiotic resource. From a wider perspective, how we represent nature creates social discourses of nature and our attitudes towards it. The results indicate that fact-based communication of nature would also benefit from the emotional effect of aesthetic imagery.